Supporting Decisions Using Educational Data Analysis - Moraes, Laura O.; Pedreira, Carlos Eduardo; Delgado, Carla; Freire, João Pedro (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2021)
We present the Machine Teaching, an online learning environment with two main goals: (1) supporting student practicing and exercise marking; and most important, (2) collecting data on students’ knowledge while they progress. Machine teaching was key to bringing programming courses to online learning during the 2020 pandemic, helping educators provide a safe and smooth online practice environment for students and helping them to master programming skills in early stages of their bachelor’s degree studies, a skill that increases the possibilities for immediate job placement. In addition, the educational data collected are mined and used to support short- and long-term pedagogical decision-making, allowing for a quick feedback and enabling material adaptations for the classes offered in the remote mode.